Acetylation inhibition alleviates energy metabolism in muscles of minipigs varying with the type of muscle fibers. (February 2022) - Yan, Jing; Nian, Yingqun; Zou, Bo; Wu, Juqing; Zhou, Guanghong; Li, Chunbao
Abstract: In this study, we investigated whether preslaughter chemical-induced acetylation affected postmortem energy metabolism and pork quality. Thirty pigs were randomly assigned to control, acetyltransferase inhibitor (ATi) or deacetyltransferase inhibitor treatments. Serum, trapezius, longissimus lumborum, psoas major, semimembranosus and semitendinosus muscles were taken for analyses. The results indicated that ATi treatment significantly reduced the activities of lactate dehydrogenase and creatine kinase and heat shock protein 70 in serum ( P  < 0.05). ATi treatment increased ATP and glycogen content, but decreased lactic acid content in trapezius, psoas major and semitendinosus muscles ( P  < 0.05). A total of 13 acetylated proteins bands were identified and the deacetylation of creatine kinase may play a key role in slowing down the postmortem energy metabolism in ATi-treated group. In addition, ATi treatment reduced the rate of postmortem glycolysis in muscles with higher oxidative but lower glycolytic fibers. These findings provide a new insight into the underlying mechanism on muscle-specific postmortem changes of pork quality. Highlights: Treatment with acetyltransferase inhibitors alleviated preslaughter stress in minipigs. Treatment with acetyltransferase inhibitors slowed down the rate of postmortem glycolysis. The effect of acetyltransferase inhibitors was more significant in muscles with higher oxidized fibers.